Extinction PC / ASA (polycarbonate / acrylonitrile-styrene-acrylate copolymer) aggregate for extruded profiles and preparation method of extinction PC / ASA aggregate
By using PC resin blended with glass fiber, inorganic filler, styrene-acrylonitrile polymer and ultrafine silica in the extruded profile, the problems of complex processing and environmental pollution of the existing extruded profile are solved, and the low gloss and high weather resistance of the material are achieved.
Patent Information
- Application Number
- CN202411989196.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
The existing extruded profile processing technology is complex and polluted the environment. PC/ASA profiles used alone have too high surface gloss, poor weather resistance and poor toughness.
The modification of PC resin is used to blend with glass fiber, inorganic filler, styrene-acrylonitrile polymer and ultrafine silica, and the modification of ASA resin and methyl methacrylate-butadiene-styrene is improved by combining matting agents and toughening agents.
The low gloss of the material is achieved, weather resistance and notch impact strength are improved, production costs are reduced, and environmental pollution caused by spray painting is avoided.
Smart Images

Figure BDA0005223259370000081 
Figure BDA0005223259370000091 
Figure BDA0005223259370000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified materials, and in particular relates to a matte PC / ASA granular material for extruded profiles and a preparation method thereof. Background Art
[0002] PC / ASA alloy combines the advantages of polycarbonate (PC) and acrylonitrile-styrene-acrylic rubber terpolymer (ASA). It has the characteristics of high strength, good toughness, high heat resistance, good weather resistance and excellent processing performance. It has been widely used in the fields of automobiles and building materials. However, ordinary PC / ASA alloy has a high glossiness. It is easy to reflect light when directly used in automobile interiors, which will cause visual fatigue to the driver. When used for extruded profiles and used with aluminum alloy doors and windows, the apparent glossiness of the two is significantly different, affecting the visual effect. Therefore, in order to meet the requirements of automotive interior materials, extruded profiles, etc. for glossiness, most of these products have been sprayed with matte paint to achieve low glossiness in the past. However, spraying paint has a large environmental pollution. At present, more and more manufacturers have begun to use low-gloss PC / ASA alloys, which eliminates the step of spraying paint, not only improving production efficiency and qualified rate, but also reducing production costs. However, the current preparation of low-gloss PC / ASA alloys mostly adopts the method of adding fillers, but this method has a great impact on the toughness of the material while reducing the glossiness, and is not suitable for the preparation of high-toughness PC / ASA alloys.
[0003] Traditional extrusion profiles are processed with various types of foam composite boards as the base layer, and the surface layer needs to be completed by plastic board pasting, painting, PMMA or ASA co-extrusion and other complex processes. Although the painting technology has been developed and widely used in production and daily life, it still has certain pollution and harm to the environment.
[0004] In recent years, traditional spray-painted profiles have been gradually replaced by more environmentally friendly matte extrusion profiles. In the production process of matte extrusion profiles, no adhesive is used. Therefore, in matte extrusion profiles, there will be no environmental pollution problems caused by adhesives, such as excessive residual solvents in adhesives. The production of matte extrusion profiles can achieve clean production and good safety during the production process. It will not pollute the surrounding environment and has good adaptability to environmental protection. It is a typical clean production process. Since the production of matte extrusion profiles uses PC / ASA pellets as raw materials, matte extrusion profiles are directly produced without intermediate products, the production process is short, and the energy and manpower consumption itself is reduced.
[0005] The matte co-extruded profiles currently available on the market all have the following defects:
[0006] 1. The surface gloss is too high, the visual effect is poor, and there is light pollution;
[0007] 2. Poor weather resistance. After long-term exposure to sunlight, it will cause discoloration, which is manifested as a large color difference value after the accelerated aging test of the material;
[0008] 3. Poor toughness, the product is prone to brittle cracking during assembly or use. Summary of the invention
[0009] In order to solve the problems of complex processing and environmental pollution of traditional extruded profiles, and excessive surface gloss, poor weather resistance, and poor toughness when using PC / ASA profiles alone, the present invention provides a matte PC / ASA granular material for extruded profiles and a preparation method thereof. The surface gloss of the product can be reduced by blending PC resin with glass fiber, inorganic filler, styrene-acrylonitrile polymer and ultrafine silica, and the modification of ASA resin and methyl methacrylate-butadiene-styrene improves the notched impact strength without affecting the weather resistance.
[0010] In order to achieve the above technical objectives, a technical solution of the present invention is:
[0011] A matte PC / ASA granules for extrusion profiles, the quality formula is as follows:
[0012] 60-80 parts of PC resin, 10-20 parts of ASA resin, 5-15 parts of toughening agent, 5-10 parts of composite matting agent, 5-10 parts of glass fiber, 5-10 parts of inorganic filler, 1-2 parts of lubricant and 1-2 parts of antioxidant; the composite matting agent adopts a composite matting modification system of styrene-acrylonitrile polymer and ultrafine silica.
[0013] The above technical solution has the following beneficial effects:
[0014] In the matte PC / ASA pellet formula for extruded profiles, the composite matting agent adopts a composite matting modification system of styrene-acrylonitrile polymer and ultrafine silica. Styrene-acrylonitrile polymer uses the micro-gelation effect caused by the incompatibility of the two substances or chemical cross-linking to cause a micro-rough effect on the surface of the material. When light is incident, diffuse reflection is formed, thereby achieving the purpose of matting, which is also helpful to improve the weather resistance of the material. Ultrafine silica has a high refractive index and transmittance. When light passes through silica particles, multiple refractions and reflections will occur, resulting in multiple scattering effects, which will change the direction of the light when it propagates in the material, thereby reducing the transmittance of the light and achieving the matting effect.
[0015] Preferably, the composite matting agent adopts a composite matting modification system of styrene-acrylonitrile polymer and ultrafine silica, and the mass ratio of styrene-acrylonitrile polymer to ultrafine silica is 2:1 to 4:1; since ultrafine silica is an inorganic compound, but its essence is still a powdered mineral, it has poor compatibility with PC resin and has a certain upper limit on the matting effect. After adding styrene-acrylonitrile polymer, the incompatibility of styrene-acrylonitrile and PC resin is utilized, the surface morphology of the product is significantly changed, better matting requirements can be met, and a good synergistic effect is achieved.
[0016] Preferably, the ASA resin is powdered ASA resin, and the acrylic rubber content of the powdered ASA resin is ≥60%, and the styrene content is <3000ppm. The ASA resin replaces the butadiene rubber containing unsaturated double bonds in ABS with acrylic rubber without unsaturated double bonds, so it can not only resist degradation, aging, and fading caused by ultraviolet radiation, but also protect against decomposition or discoloration caused by high temperature during oxidation processing in the atmosphere, thereby greatly improving the material's anti-aging and weather resistance; the acrylic rubber component therein can also improve the notched impact strength of the PC resin and increase the toughness of the PC / ASA alloy.
[0017] Preferably, the toughening agent is at least one of an acrylic toughening agent, a methyl methacrylate-butadiene-styrene toughening agent and a silicon toughening agent; the PC resin molecular chain contains a large number of benzene rings, which makes the molecular chain difficult to move, thereby making the PC melt viscosity larger. During the processing, the PC molecular chain is oriented, which will cause a large amount of residual stress in the product, thereby causing the product to have brittle cracking. These three toughening agents are core-shell impact modifiers. Among them, the acrylate toughening agent has acrylate as the core and acrylate and methyl methacrylate copolymer as the shell; the methyl methacrylate-butadiene-styrene toughening agent has a core-shell structure with butadiene as the core and styrene-methyl methacrylate copolymer as the shell; the silicone toughening agent has silicone and acrylate as the core and methyl methacrylate as the shell; after the toughening agent is added to the PC / ASA resin, the cross-section of the PC / ASA becomes rough and distributed in a fish-scale shape. At the same time, multiple obvious voids appear, and small balls are found in the voids. These small balls are evenly dispersed and uniform in size. This is the "core" in the core-shell structure. When subjected to external force, these small balls will act as stress concentration points, absorb and dissipate energy, and play a role in producing silver streaks and preventing further development of cracks.
[0018] Preferably, the glass fiber is at least one of chopped glass fiber, ground glass fiber powder, glass beads or flat glass fiber; PC / ASA resin modified by glass fiber can greatly improve the tensile strength and modulus of the material, while greatly improving the dimensional stability and heat resistance of the material. Glass fiber added to PC / ASA resin has a reinforcing effect and improves the physical and mechanical properties of the product; after glass fiber is added to PC / ASA resin, due to the irregular orientation of glass fiber in the resin, uneven pits will be formed on the surface of the resin, and these pits can absorb part of the light to form diffuse reflection, thereby enhancing the matte effect of PC / ASA alloy.
[0019] Preferably, the inorganic filler is at least one of needle-shaped wollastonite, nano-scale calcium carbonate and flaky talc; needle-shaped wollastonite is similar to glass fiber, less oriented in the thickness direction, partially replaces short glass fiber, improves thermal conductivity and dimensional stability, reduces linear expansion coefficient, improves scratch resistance, improves heat deformation temperature, and improves low-temperature impact / thermal collapse performance; nano-scale calcium carbonate has good affinity for PC resin, can effectively increase or adjust the rigidity and toughness of the material, as well as bending strength, and can improve the rheological properties of the processing system, reduce the plasticizing temperature and surface gloss, and improve the dimensional stability and heat resistance of the product; flaky talc has a large diameter-to-thickness ratio and may be enriched on the surface of the product, and a certain plane flipping occurs, resulting in a slightly rough surface of the product, with a certain matting effect.
[0020] Preferably, the lubricant is at least one of silicone masterbatch and pentaerythritol tetrastearate; silicone masterbatch can effectively increase the melting rate of PC / ASA alloy, reduce viscosity and improve plasticization, prevent melt fracture, improve the wear resistance, corrosion resistance and aging resistance of the surface of plastic products, and improve the compatibility between resin and filler; pentaerythritol tetrastearate has good thermal stability and low volatility, good demoulding and flow properties at high temperatures, plays a lubricating role in the melting process of PC resin, prevents the molten plastic from adhering to the mold and equipment, and can make the product demould smoothly in a high temperature environment, even in a mold with a complex structure, it can ensure good demoulding properties, and has an excellent nucleation effect on partially crystallized plastics.
[0021] In order to achieve the above technical objectives, the present invention also provides a method for preparing the above-mentioned matte PC / ASA pellets for extrusion profiles, the steps comprising:
[0022] Prepare PC resin, ASA resin, toughening agent, composite matting agent, glass fiber, inorganic filler, lubricant, and antioxidant according to the formula ratio;
[0023] Add PC resin, ASA resin, toughening agent, composite matting agent, inorganic filler, lubricant and antioxidant into a high-speed mixer and stir until fully mixed to obtain a premixed powder;
[0024] Add glass fiber to premixed powder, stir at low speed in a low-speed mixer for 5 to 10 minutes until fully mixed to obtain mixed powder; then place in a parallel twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain matte PC / ASA pellets for extrusion profiles.
[0025] The above preparation method has the following advantages:
[0026] Through a simple and efficient mixing and granulation process, physical modification of PC / ASA resin, composite matting agent and weathering modifier is achieved, the surface gloss of PC / ASA resin is reduced, and the weathering and impact resistance of the product are improved.
[0027] Preferably, the stirring and mixing temperature of the high-speed mixer is 60-80° C. The temperature of 60-80° C. helps other additives to penetrate into the gaps of the PC / ASA resin, so that the additives are evenly dispersed in the PC / ASA resin.
[0028] Preferably, the stirring and mixing temperature of the low-speed mixer is 40-50°C, the aspect ratio of the parallel twin screws of the twin-screw extruder is 36:1-40:1, the screw speed is 300-500r / min, the extrusion granulation temperature is 220-260°C, and the residence time is 1-2min. After low-speed mixing, the filler, glass fiber and PC resin particles are completely mixed to prevent the problems of glass fiber agglomeration and pilling caused by high-speed stirring. DETAILED DESCRIPTION
[0029] The following describes the embodiments of the present invention in detail, but does not limit the claims of the present invention in any way.
[0030] The invention solves the problems that the existing plastic extrusion profiles use various foam composite boards as the base layer, and the surface layer needs to be made of plastic board pasting, spray painting, PMMA or ASA co-extrusion, which is complicated and polluting to the environment; and the use of PC profiles alone has the problems of too high surface gloss and too high cost. The invention provides a matte PC / ASA pellet formula for extrusion profiles, and the proportions of each component are as follows (by mass):
[0031] 60-80 parts of PC resin;
[0032] 10-20 parts of ASA resin, which can be powdered ASA resin, and the acrylic rubber content in the powdered ASA resin is ≥60%, and the styrene content is <3000ppm, preferably Japanese UMG A600N and Shandong Ruifeng RF-2660;
[0033] 5 to 15 parts of a toughening agent, which may be at least one of an acrylic toughening agent, a methyl methacrylate-butadiene-styrene toughening agent, and a silicon toughening agent, preferably a methyl methacrylate-butadiene-styrene toughening agent;
[0034] 5-10 parts of composite matting agent, which can be a composite matting system of styrene-acrylonitrile polymer and ultrafine silica, and the mass ratio of styrene-acrylonitrile polymer to ultrafine silica is 2:1-4:1, preferably 2:1;
[0035] 5-10 parts of glass fiber, which can be at least one of chopped glass fiber, ground glass fiber powder, glass micro beads or flat glass fiber, preferably flat glass fiber;
[0036] 5-10 parts of inorganic filler, which can be at least one of needle-shaped wollastonite, nano-scale calcium carbonate and flaky talc, preferably flaky talc;
[0037] 1-2 parts of lubricant, which can be at least one of silicone masterbatch and pentaerythritol tetrastearate;
[0038] 1 to 2 parts of antioxidant, at least one of antioxidant 168 and antioxidant 1076 can be selected.
[0039] In the above recipe:
[0040] (1) The composite matting agent adopts a composite matting modification system of styrene-acrylonitrile polymer and ultrafine silica. Styrene-acrylonitrile polymer uses the micro-gelation effect caused by the incompatibility of the two substances or chemical cross-linking to create a micro-rough effect on the surface of the material. When light enters, diffuse reflection is formed, thereby achieving the purpose of matting, which is also helpful to improve the weather resistance of the material. Ultrafine silica has a high refractive index and light transmittance. When light passes through silica particles, multiple refractions and reflections will occur, resulting in multiple scattering effects, causing the direction of light to change when it propagates in the material, thereby reducing the transmittance of light and achieving a matting effect. Since ultrafine silica is an inorganic compound, but its essence is still a powdered mineral, it has poor compatibility with PC resin and has a certain upper limit on the matting effect. After adding styrene-acrylonitrile polymer, the incompatibility of styrene-acrylonitrile and PC resin is utilized to significantly change the surface morphology of the product, which can meet better matting requirements and achieve a good synergistic effect.
[0041] (2) ASA resin uses powdered ASA resin, and the acrylic rubber content of the powdered ASA resin is ≥60%, and the styrene content is <3000ppm. ASA resin replaces the butadiene rubber containing unsaturated double bonds in ABS with acrylic rubber without unsaturated double bonds. Therefore, it can not only resist degradation, aging, and fading caused by ultraviolet radiation, but also protect against decomposition or discoloration caused by high temperature during oxidation processing in the atmosphere, thereby greatly improving the material's anti-aging and weather resistance. The acrylic rubber component therein will also improve the notched impact strength of PC resin and increase the toughness of PC / ASA alloy.
[0042] (3) The toughening agent is at least one of an acrylic toughening agent, a methyl methacrylate-butadiene-styrene toughening agent, and a silicon toughening agent; the PC resin molecular chain contains a large number of benzene rings, which makes the molecular chain difficult to move, resulting in a large viscosity of the PC melt. During the processing, the PC molecular chain is oriented, which will cause a large amount of residual stress in the product, resulting in brittle cracking of the product. These three toughening agents are core-shell impact modifiers. Among them, the acrylate toughening agent has acrylate as the core and acrylate and methyl methacrylate copolymer as the shell; the methyl methacrylate-butadiene-styrene toughening agent has a core-shell structure with butadiene as the core and styrene-methyl methacrylate copolymer as the shell; the silicone toughening agent has silicone and acrylate as the core and methyl methacrylate as the shell; after the toughening agent is added to the PC / ASA resin, the cross-section of the PC / ASA becomes rough and distributed in a fish-scale shape. At the same time, multiple obvious voids appear, and small balls are found in the voids. These small balls are evenly dispersed and uniform in size. This is the "core" in the core-shell structure. When subjected to external force, these small balls will act as stress concentration points, absorb and dissipate energy, and play a role in producing silver streaks and preventing further development of cracks.
[0043] (4) The glass fiber is at least one of chopped glass fiber, ground glass fiber powder, glass microbeads or flat glass fiber; PC / ASA resin modified by glass fiber can greatly improve the tensile strength and modulus of the material, and at the same time greatly improve the dimensional stability and heat resistance of the material. The glass fiber added to the PC / ASA resin has a reinforcing effect and improves the physical and mechanical properties of the product; after the glass fiber is added to the PC / ASA resin, due to the irregular orientation of the glass fiber in the resin, uneven pits will form on the surface of the resin, and these pits can absorb part of the light, forming a diffuse reflection phenomenon, thereby enhancing the matte effect of the PC / ASA alloy.
[0044] (5) The inorganic filler is at least one of needle-shaped wollastonite, nano-scale calcium carbonate and flaky talc; needle-shaped wollastonite is similar to glass fiber, less oriented in the thickness direction, partially replaces short glass fiber, improves thermal conductivity and dimensional stability, reduces linear expansion coefficient, improves scratch resistance, increases heat deformation temperature, and improves low-temperature impact / thermal collapse performance; nano-scale calcium carbonate has good affinity for PC resin, can effectively increase or adjust the rigidity and toughness of the material, as well as bending strength, and can improve the rheological properties of the processing system, reduce the plasticizing temperature and surface gloss, and improve the dimensional stability and heat resistance of the product; flaky talc has a large diameter-to-thickness ratio and may be enriched on the surface of the product, and a certain plane flipping occurs, resulting in a slightly rough surface of the product, with a certain matte effect.
[0045] (6) The lubricant is at least one of silicone masterbatch and pentaerythritol tetrastearate; silicone masterbatch can effectively increase the melting rate of PC / ASA alloy, reduce viscosity and improve plasticization, prevent melt fracture, improve the wear resistance, corrosion resistance and aging resistance of the surface of plastic products, and improve the compatibility between resin and filler; pentaerythritol tetrastearate has good thermal stability and low volatility at high temperatures, good demolding and flow properties, and plays a lubricating role in the melting process of PC resin, preventing the molten plastic from adhering to the mold and equipment. At the same time, it can make the product demold smoothly under high temperature environment, and can ensure good demolding properties even in molds with complex structures, and has an excellent nucleation effect on partially crystallized plastics.
[0046] A preparation method is provided based on the above formulation, the steps comprising:
[0047] Prepare PC resin, ASA resin, toughening agent, composite matting agent, glass fiber, inorganic filler, lubricant, and antioxidant according to the formula ratio;
[0048] Add PC resin, ASA resin, toughening agent, composite matting agent, inorganic filler, lubricant and antioxidant into a high-speed mixer and stir until fully mixed to obtain a premixed powder. The stirring and mixing temperature is 60-80°C.
[0049] Add glass fiber to premixed powder, stir at low speed for 5 to 10 minutes in a low-speed mixer until completely mixed, the stirring and mixing temperature is 40 to 50° C., to obtain a mixed powder; then place the mixed powder in a parallel twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain matte PC / ASA pellets for extrusion profiles, the parallel twin screws of the twin-screw extruder have an aspect ratio of 36:1 to 40:1, a screw speed of 300 to 500 r / min, an extrusion granulation temperature of 220 to 260° C., and a residence time of 1 to 2 minutes.
[0050] According to the above-mentioned method for preparing matt PC / ASA pellets for extrusion profiles, six kinds of matt PC / ASA pellets for extrusion profiles are specifically prepared. The proportions (in parts by mass) of the formulation components in the six implementation schemes (Examples 1 to 6) are shown in Table 1:
[0051] Table 1 Recipe group distribution ratio table (unit: portion)
[0052]
[0053]
[0054] The matte PC / ASA pellets for extrusion profiles prepared in the six embodiments in Table 1 and the commercially available PC for extrusion profiles in the comparative example were tested, and the test results are shown in Table 2:
[0055] Table 2 Performance test results comparison table
[0056]
[0057] In Table 2:
[0058] (1) The surface gloss is tested according to GB8807 at an angle of 60°;
[0059] (2) Weather resistance (100-hour △E color difference) was tested in accordance with GB / T16422.3-2022, using UVA-340 lamps with an irradiance of 0.76w / m 2 (340nm), blackboard temperature is 60℃, 8h, condensation temperature is 50℃, 4h; the color change of the sample surface is tested every 50h, and a total of three tests are performed;
[0060] (3) The cantilever beam notched impact strength is tested in accordance with GB / T1843 using a 2.75J pendulum.
[0061] As can be seen from Table 2, the matte PC / ASA pellets for extruded profiles prepared by the formula and preparation method proposed in the present invention have better surface gloss and weather resistance than PC for commercially available extruded profiles, among which Examples 2 and 5 have the best performance. Therefore, the matte PC / ASA pellets for extruded profiles proposed in the present invention have good matte effect and weather resistance.
[0062] In summary, the present invention has the following advantages:
[0063] 1. The present invention solves the problem that the existing plastic extrusion profiles use various types of foamed composite boards as the base layer, and the surface layer needs to be made of plastic board pasting, spray painting, PMMA or ASA co-extrusion, which is complicated and polluting to the environment;
[0064] 2. The present invention solves the problems of excessive surface gloss and high cost when using PC profiles alone. The surface gloss of the product can be reduced by blending PC resin with glass fiber, inorganic filler, styrene-acrylonitrile polymer and ultrafine silica. The modification of ASA resin and methyl methacrylate-butadiene-styrene improves the notched impact strength without affecting the weather resistance.
[0065] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A matte PC / ASA granular material for extrusion profiles, characterized in that: Its quality formula is as follows: 60-80 parts of PC resin, 10-20 parts of ASA resin, 5-15 parts of toughening agent, 5-10 parts of composite matting agent, 5-10 parts of glass fiber, 5-10 parts of inorganic filler, 1-2 parts of lubricant, 1-2 parts of antioxidant; The composite matting agent adopts a composite matting modification system of styrene-acrylonitrile polymer and ultrafine silicon dioxide.
2. The matte PC / ASA granules for extrusion profiles according to claim 1, characterized in that: The composite matting agent adopts a composite matting modification system of styrene-acrylonitrile polymer and ultrafine silicon dioxide, and the mass ratio of styrene-acrylonitrile polymer to ultrafine silicon dioxide is 2:1-4:
1.
3. The matte PC / ASA granules for extrusion profiles according to claim 1, characterized in that: The ASA resin is powdered ASA resin, and the acrylic rubber content in the powdered ASA resin is ≥60%, and the styrene content is <3000ppm.
4. The matte PC / ASA granules for extrusion profiles according to claim 1, characterized in that: The toughening agent is at least one of an acrylic toughening agent, a methyl methacrylate-butadiene-styrene toughening agent and a silicon toughening agent.
5. The matte PC / ASA granules for extrusion profiles according to claim 1, characterized in that: The glass fiber is at least one of chopped glass fiber, ground glass fiber powder, glass microbeads and flat glass fiber.
6. The matte PC / ASA granules for extrusion profiles according to claim 1, characterized in that: The inorganic filler is at least one of needle-shaped wollastonite, nano-scale calcium carbonate and flaky talc.
7. The matte PC / ASA granules for extrusion profiles according to claim 1, characterized in that: The lubricant is at least one of silicone masterbatch and pentaerythritol tetrastearate.
8. A method for preparing the matte PC / ASA pellets for extrusion profiles according to any one of claims 1 to 7, comprising: Prepare PC resin, ASA resin, toughening agent, composite matting agent, glass fiber, inorganic filler, lubricant, and antioxidant according to the formula ratio; Add PC resin, ASA resin, toughening agent, composite matting agent, inorganic filler, lubricant and antioxidant into a high-speed mixer and stir until fully mixed to obtain a premixed powder; Add glass fiber to premixed powder, stir at low speed in a low-speed mixer for 5 to 10 minutes until fully mixed to obtain mixed powder; then place in a parallel twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain matte PC / ASA pellets for extrusion profiles.
9. The method for preparing matt PC / ASA pellets for extrusion profiles according to claim 8, characterized in that: The stirring and mixing temperature of the high-speed mixer is 60-80°C.
10. The method for preparing matt PC / ASA granules for extrusion profiles according to claim 8, characterized in that: The stirring and mixing temperature of the low-speed mixer is 40-50° C., the length-diameter ratio of the parallel twin screws of the twin-screw extruder is 36:1-40:1, the screw speed is 300-500 r / min, the extrusion granulation temperature is 220-260° C., and the residence time is 1-2 min.